Self-extensional space in relocated housing after 2004 indian ocean tsunami: Case study of namkem community, PhangNga, Thailand - Titaya Sararit (2018)
© 2018, Fuji Technology Press. All rights reserved. This study focuses on some houses in Phang Nga Province in Thailand that were permanently relocated after the Indian Ocean tsunami in 2004. It aims to analyze extensions and improvements by residents who have lived in the houses for a long time. Most previous research has painted spatial extensions in a bad light because of the negative feedback from residents regarding post-disaster housing; this could mean that residents were less than satisfied with such houses in comparison to their previous ones with respect to construction, function, or size. Observing and interviewing residents allowed me to infer that spatial extensions can also represent the positive development of long-term recovery projects, as they increase the satisfaction of residents who, more than 10 years after the tsunami, have changed their lifestyles, family sizes, and jobs. It also demonstrates why residents are more satisfied with house types that allow them to carry out the required space adaptions or extensions when they have an increase in their income. In this study, it was observed that extensional space could also be a positive factor revealing the developments in residents’ lives as they showed their intent to live permanently in this type of housing even after the disaster.